Natıonal Alms Instıtutıons’ Perspectıve Towards Exıstence And Problems On Rule Of Natıonal Alms Instıtutıons In Desıgnıng And Workıng Procedure Upz Issue 2, Season 2016 In Jambı Cıty - Muhammad Amin Qodri; Umar Hasan; Evalina Alissa; Rafiqi Rafiqi; Afi Parnawi (Cita Konsultindo Research Center, 2024)
Alms is an order as narrated by Allah swt. For Muslims, certain assets are issued and given to those who are entitled. In regulating the implementation of zakat in society, the Indonesian government establishes special institutions, namely BAZNAS and LAZ as outlined in Law Number 23 of 2011 concerning Zakat Management. Based on these regulations, the task of BAZNAS is to assist in the management of zakat by establishing UPZ, one of which is at the sub-district, village, or other names. The duties of UPZ are regulated in PERBAZNAS Number 2 of 2016 concerning the Establishment and Work Procedure of UPZ, which explains how the mechanism for the formation of UPZ and the working mechanism of UPZ in each sector. The results of this study can be concluded that the existence of UPZ from every mosque and mushalla in several sub-districts in Jambi City is still not visible. Like several mosque and mushalla administrators, it was stated that UPZ had not yet been formed and also did not know specifically about UPZ itself. The problems faced by BAZNAS Jambi City are the lack of personnel from Jambi City BAZNAS employees in an effort to reach mosques and prayer rooms in Jambi City, lack of operational costs in socializing, the higher volume of work faced by BAZNAS. So that the Jambi City BAZNAS is expected to focus more on the work pattern mandated by PERBAZNAS Number 2 of 2016, so that there are no more mosques or mushalla whose UPZ has not been formed.